Applying Lean Six Sigma tools to reduce the rate of slips, trips and falls for Joint Commission field staff. (2015) - Kubilius, Andrius; Winfrey, Keith; Mayer, Carrie; Johnson, Gregory; Wilson, Teena
This paper presents how the Lean Six Sigma DMAIC methodology and change management tools are used to reduce the rate of slips, trips and falls (STFs) for Joint Commission field staff. The data sources included Workmen's Compensation claims data and an online survey (N = 453, response rate = 64%) administered to field staff who reported workplace STFs. The metric for this project: "Falls per opportunity based upon 1, 000 surveyor days" had a pre-intervention (1/2007-4/2010) rate of field staff STFs of 0.339 and a post-intervention (5/2010-2/2014) rate of field staff STFs of 0.116 per 1000 surveyor days. Multiple risk factors are associated with field staff STFs consisting of environmental factors and individual behaviours. Targeted solutions included seasonal e-mails to raise staff awareness on footwear and changing weather conditions, as well as an informational pamphlet about the risks associated with walking surface conditions, carrying work-related or personal items, and type of luggage used.